Endophytes from wheat as biocontrol agents against tan spot disease - Larran, S. (2016)
Endophytes from wheat cultivars isolated in Buenos Aires province, Argentina, were assessed for their potential as biocontrol agents againstPyrenophora tritici-repentis(Died.) Drechsler (anamorphDrechslera tritici-repentis) (Died.) Shoem (Dtr), the causal agent of tan spot of wheat. Endophytes were screened using dual culture techniques and examining the effect on growth, sporulation and the antifungal activity in greenhouse assays. The most of endophytes tested significantly reducedDtrgrowth compared to the control exceptRhodotorula rubrafrom 11 to 15days post inoculation.Trichoderma hamatum,Penicilliumsp.,Bacillussp. andPaecilomyces lilacinussignificantly reduced the colony diameter of the pathogen. Most of the endophytes evaluated showed morphological changes in the conidia and/or the mycelia ofD. tritici-repentis. In addition, two endophytes,Bacillussp. andFusariumsp., reduced significantly the percent spore germination ofDtrcompared to the control by 82% and 52% respectively. In greenhouse experimentT. hamatum,Chaetomium globosumandFusariumsp. significantly (P⩽0.05) reduced the average disease severity on all three leaves compared to the control. However, the best antagonistic effect was shown withT. hamatumas it resulted in the greatest suppression in the greenhouse and in the dual-plate assays. Likewise,Bacillussp. was other highlighted microorganism that antagonized the pathogen inin vitroassays. From our promising results, we conclude that endophytes have potential in the biological control of tan spot of wheat caused byD. tritici-repentis, particularlyT. hamatumandBacillussp.